Studies in Mahimabhaṭṭa : a critical and comparative study of Mahimabhaṭṭa's Vyaktiviveka - Chakravorty, Amiya Kumar, 1910- (Calcutta University, 1975)
Criticism and interpretation of an 11th century treatise on Sanskrit poetics, refuting the theory of suggested meaning (dhvani) of Anandavardhana according to the theory of oblique statement (vakrokti) of Kuntaka.